DIGITAL BLOCK APPLICATIONS; A DETAILED SURVEY BETWEEN SURGICAL BRANCH SPECIALIST AND SPECIALIST STUDENTS - Taşova, Ali Osman; Sürecek, Mustafa Cem (International Journal of Research -GRANTHAALAYAH, 2025)
Purpose: The purpose of this study was to investigate the digital block application methods of specialists and assistants working in the Departments of Orthopedics and Traumatology, Emergency Medicine, Anesthesia and Reanimation, and Plastic and Reconstructive Surgery in Turkey and the accuracy of the information on which these methods are based, through a survey, and to interpret the survey results. Study plan: In the survey consisting of a total of eighteen questions, the personal information of the physicians, their preferred digital block application methods, local anesthetic agent selection and application doses, and the source of the information on which these preferences are based were questioned in a digital environment. The responses were interpreted and analyzed. Findings: A total of 110 physicians, 16 specialists and 94 assistants, participated in our survey. In the responses given to the multiple-choice question asked to the participants about the cases you encounter most frequently in your clinic, we saw that the most common ones were fractures at the finger and toe level, skin and subcutaneous lacerations at the finger level, and tendon injuries. In the responses we received to the question of the most preferred type of anesthesia in such injuries, we saw that 51.9% preferred digital block and 42.6% preferred regional anesthesia. In the responses we received to other questions regarding the application method, dosage and different usage patterns in our survey, it was seen that traditional and personal experiences were effective in digital block applications. Conclusion: It was determined that the digital nerve block applications preferred by specialists and specialist students were not compatible with the literature. The results of the study are warning signs for the revision of digital block applications. Experience-based applications and personal teachings should be replaced by evidence-based applications in digital block applications.